2013
DOI: 10.1371/journal.pone.0078063
|View full text |Cite
|
Sign up to set email alerts
|

Specifically Expressed Genes of the Nematode Bursaphelenchus Xylophilus Involved with Early Interactions with Pine Trees

Abstract: As the causal agent of pine wilt disease (PWD), the pine wood nematode (PWN), Bursaphelenchus xylophilus, causes huge economic losses by devastating pine forests worldwide. However, the pathogenesis-related genes of B. xylophilus are not well characterized. Thus, DNA microarrays were used to investigate differential gene expression in PWN where Pinus thunbergii was inoculated with nematodes, compared with those cultured on Botrytis cinerea. The microarrays comprised 31121 probes, 1310 (4.2%) of which were diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…S2). Qiu et al (2013) showed that the expression of Bxcht-1 was downregulated dramatically when B. xylophilus was used to inoculate Pinus thunbergii compared with the PWN culture on B. cinerea, suggesting that this chitinase gene is, in fact, responsible for chitin degradation when the nematode feeds on fungi. This result suggests that in the presence of bacteria the PWN does not express the Bxcht-1 gene, thus, supporting our hypothesis.…”
Section: Strain Bxf1 Effect On Pwn Reproductionmentioning
confidence: 99%
“…S2). Qiu et al (2013) showed that the expression of Bxcht-1 was downregulated dramatically when B. xylophilus was used to inoculate Pinus thunbergii compared with the PWN culture on B. cinerea, suggesting that this chitinase gene is, in fact, responsible for chitin degradation when the nematode feeds on fungi. This result suggests that in the presence of bacteria the PWN does not express the Bxcht-1 gene, thus, supporting our hypothesis.…”
Section: Strain Bxf1 Effect On Pwn Reproductionmentioning
confidence: 99%
“…For example, one study has used proteomics analysis of secreted proteins collected from nematodes stimulated with pine extracts and identified cell wall-degrading enzymes, detoxification enzymes and peptidases amongst the secreted proteins (Shinya et al, 2013). In an alternative approach, microarray analysis has been used to identify secreted proteins up-regulated during infection (Qiu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the expression of genes encoding antioxidant proteins may be a response to host‐derived ROS. These genes were identified here and were also expressed in B. xylophilus 7 days after infection in pine trees (Qiu et al ., ). Bursaphelenchus xylophilus is known to produce surface coat proteins to help protect itself from ROS (Shinya et al ., ).…”
Section: Discussionmentioning
confidence: 97%